Chiral assembly of organic luminogens with aggregation-induced emission. Issue 3 (10th June 2021) - Liu, Chenchen; Yang, Jun-Cheng; Lam, Jacky W. Y.; Feng, Hai-Tao; Tang, Ben Zhong
Abstract : This review highlights the recent development of chiral materials with aggregation-induced emission properties, including their molecular structures, self-assembly and functions. Abstract : Chirality is important to chemistry, biology and optoelectronic materials. The study on chirality has lasted for more than 170 years since its discovery. Recently, chiral materials with aggregation-induced emission (AIE) have attracted increasing interest because of their fascinating photophysical properties. In this review, we discussed the recent development of chiral materials with AIE properties, including their molecular structures, self-assembly and functions. Generally, the most effective strategy to design a chiral AIE luminogen (AIEgen) is to attach a chiral scaffold to an AIE-active fluorophore through covalent bonds. Moreover, some propeller-like or shell-like AIEgens without chiral units exhibit latent chirality upon mirror image symmetry breaking. The chirality of achiral AIEgens can also be induced by some optically active molecules through non-covalent interactions. The introduction of an AIE unit into chiral materials can enhance the efficiency of their circularly polarized luminescence (CPL) in the solid state and the dissymmetric factors of their helical architectures formed through self-assembly. Thus, highly efficient circularly polarized organic light-emitting diodes (CPOLEDs) with AIE characteristics are developed and show great potential in 3D displays. Chiral AIEgens are also widely utilized as "turn on" sensors for rapid enantioselective determination of chiral reagents. It is anticipated that the present review can entice readers to realize the importance of chirality and attract much more chemists to contribute their efforts to chirality and AIE study.